2020
DOI: 10.15835/nbha48111762
|View full text |Cite
|
Sign up to set email alerts
|

The chloroplast localization of protease mediated by the potato rbcS signal peptide and its improvement for construction of photorespiratory bypasses

Abstract: Location of the proteases would affect on protease stability and photorespiratory bypass pathway, while it is unsolved. Potato rbcS signal peptide was analyzed and constructed into the protease for study of their localization site. The tartronate semialdehyde reductase (EcTSR) proteins could be accurately and efficiently located in chloroplast only when this signal peptide was extended to 80 amino acids. The signal peptide would help malate synthase (CmMS) locate to the surface of chloroplast, to form granules… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Notably, however, some novel cTPs have been designed to reduce the proteolytic scars while enhancing targeting of difficult protein cargoes. These engineered cTPs, such as RC2 and PC1 ( Shen et al, 2017 ; Yao et al, 2020 ) include about 20 residues from its native mature cargo (a spacer to allow translocating factors better access to the cTP) which are followed by a second SPP cleavage site (to allow removal of the additional 20 residues used as spacer). Another approach that has been specifically used for the HCO 3 − transporters SbtA and BicA included a TEV protease cleavage site after the cTP to enable removal by a heterologously expressed TEV protease ( Uehara et al, 2016 , 2020 ).…”
Section: How Can We Get C I Uptake Systems Into the Chloroplast?mentioning
confidence: 99%
“…Notably, however, some novel cTPs have been designed to reduce the proteolytic scars while enhancing targeting of difficult protein cargoes. These engineered cTPs, such as RC2 and PC1 ( Shen et al, 2017 ; Yao et al, 2020 ) include about 20 residues from its native mature cargo (a spacer to allow translocating factors better access to the cTP) which are followed by a second SPP cleavage site (to allow removal of the additional 20 residues used as spacer). Another approach that has been specifically used for the HCO 3 − transporters SbtA and BicA included a TEV protease cleavage site after the cTP to enable removal by a heterologously expressed TEV protease ( Uehara et al, 2016 , 2020 ).…”
Section: How Can We Get C I Uptake Systems Into the Chloroplast?mentioning
confidence: 99%
“…Previous studies have confirmed the importance of photorespiration metabolic pathway in Arabidopsis (Kebeish et al, 2007;Maier et al, 2012), rice (Shen et al, 2019) and potato (Nölke et al, 2014) in boosting biomass and minimizing the harm caused by CO 2 deficits and surplus energy under abiotic stress such as high temperature and drought conditions. Reducing the loss of carbon, nitrogen, and energy by diverting glycolic acid produced by RuBP (1,5-ribulose diphosphate) oxidation; avoiding the toxicity of metabolizing photorespiration intermediates; and enhancing photosynthesis and biomass production are the common points of the three effective photorespiration branches (Maier et al, 2012;Dalal et al, 2015;Shen et al, 2019;Yao et al, 2020). Kebeish et al (2007), introduced five genes from bacteria metabolizing glycolate into Arabidopsis, resulting in transformed plants capable of directly converting the glycolate of chloroplasts into glycerate.…”
Section: Introductionmentioning
confidence: 99%